The Effect of Service Quality, Information Quality and System Quality on Compliance Taxpayer(Study on Taxpayers at the BPKAD of Karangasem Regency) - Diki Alvian Alvian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Taxpayer compliance remains a serious challenge in regional tax management, particularly in Karangasem Regency, which has experienced high levels of tax arrears during the 2021–2023 period. This study aims to empirically examine the influence of service quality, information quality, and system quality on taxpayer compliance. The research object includes all active regional taxpayers registered at the Regional Financial and Asset Management Agency (BPKAD) of Karangasem Regency. A total of 100 respondents were selected using purposive sampling based on specific respondent criteria. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that service quality, information quality, and system quality have a positive influence on taxpayer compliance. These findings suggest a unidirectional relationship, where improvements in service quality, clarity of information, and the reliability of administrative systems lead to increased levels of taxpayer compliance. This study has limitations in terms of the number of variables examined and the dominance of respondents from land and building tax (PBB-P2), so the results do not fully represent the diversity of influencing factors and types of regional taxes.